EKSPLORASI ETNOMATEMATIKA PADA PERMAINAN TABAK DITINJAU DARI MATERI SEKOLAH DASAR - Listari, Dita; Handayani, Lita; Rustanuarsi, Ressy (IAIN Pontianak, 2024)
This study aims to identify the mathematical elements contained in the traditional game Tabak in Kubu Raya Regency in terms of elementary school materials. This research is an exploratory research with an ethnographic approach. The research data were obtained by observation, interview, documentation and literature study. Data analysis techniques used data condensation, data display, and conclusion drawing. The results of this study show that the traditional game Tabak has mathematical elements that are relevant to the mathematics material taught at the elementary school level. The elements of mathematics include 2D shapes and their properties, cuboid, angles, relationships between lines, counting, and fractions.